Cucurbitacin B Induces Hypoglycemic Effect in Diabetic Mice by Regulation of AMP-Activated Protein Kinase Alpha and Glucagon-Like Peptide-1 via Bitter Taste Receptor Signaling - Kim, Kang-Hoon; Lee, In-Seung; Park, Ji Young; Kim, Yumi; An, Eun-Jin; Jang, Hyeung-Jin (Frontiers in Pharmacology, 2018)
Taste receptors exist in several organs from tongue to colon and have diverse functions dependent on specific cell type. In enteroendocrine L-cells, stimulation of taste receptor signaling induces incretin hormones. Especially, GLP-1 induces insulinotropic action by activating GLP-1 receptor of pancreatic beta-cells although under hyperglycemic condition in T2DM patients. However, GLP-1 mimetic medicines have reported clinical side effects such as autoimmune hepatitis, acute kidney injury, pancreatitis, and pancreatic cancer. Here, we hypothesized that if natural components can activate agonistic action of taste receptor, they may stimulate GLP-1 and therefore, could be developed as an applicable medicine to T2DM without side effects. CuB is compose of triterpenoid structure and its structural character, that represents bitterness, can stimulate AMPK pathway. Ativated intestinal AMPK level, via CuB, ameliorated hyperglycemia by inducing plasma GLP-1 and insulin release in diabetic mice. This hypoglycemic action was decreased in dorsomorphin-injected mice and alpha-gust knock out mice. Moreover, systemic inhibition study in differentiated NCI-H716 cell line showed that CuB-mediated GLP-1 secretion was involved in activation of AMPK, Galpha-gust and G beta gamma-signaling. In summary, we conclude that, CuB represents a novel hypoglycemic agents by activation of AMPK and stimulation of GLP-1 in differentiated enteroendocrine L-cells. These results suggest that taste receptor signaling-based therapeutic agents within tremendously diverse natural sources, could be applied to developing therapeutics for T2DM patients.